(untitled) (Bangladesh Journal of Infectious Diseases, 2020)
Background: Expansion of Dengue fever caused by a mosquito borne arbovirus to new countries and, from urban to rural settings constitutes an important health problem in the world including Bangladesh. Objective: This study was conducted to evaluate spread of clinical Dengue to previously non-endemic Barisal district and get an idea of how recent this spread is by comparing proportions of non-travelers and travelers to an endemic area among the admitted patients. Methodology: The incidence of dengue infection in Barisal division with and without travel history to known endemic area was investigated in the current cross sectional study from a conveniently selected sample of patients admitted to the medicine department of Sher-e-Bangla medical College Hospital form Barisal district from July 15, through August, to September 15, 2019. Clinical and laboratory data were collected by attending doctors and checked by investigators. The primary diagnostic tool was NS1 antigen detected by SD Bioline Dengue NS1 Ag Test Kit. Data entry and analysis was done by SPSS version 24.0 software. Result: A total number of sample size was 212 admitted patents of whom 138(65.1%) were male, 74 (34.9 %) were female,116 (54.7%) of patients traveled to a known endemic zone, 96 (45.3%) did not; 206 (97.2%) were NS1 positive, 4 (1.9%) were IgM positive, 2 (0.9%) were IgM positive and IgG positive; Of travelling 116 patients, 92(79.3%) were male, 24(20.7%) were female, of travelling 96 patients 46(47.9%) were male, 50(52.1%) were female. p-value was <0.001. Conclusion: The study concluded that Dengue is becoming endemic in previously non-endemic zones like greater Barisal, though travelers still holds the major share of disease burden. Male preponderance in traveling to endemic zone was statistically significant. Bangladesh Journal of Infectious Diseases 2020;7(1):3-7